Making Sense of Big Data for Security - Chan, Janet B. L. (The British journal of criminology, 2017)
Big Data technologies hold great promise for improved efficiency and effectiveness for law enforcement and national security. This article explores the potential impact of Big Data on the production of security in society. Building on a Bourdesian framework for analysing police and new technologies, the article draws on empirical data from an Australian study to examine how security agents made sense of the capability and value of Big Data and developed technological frames that envisaged how this new technology could enhance or change their practices. The analysis reveals the expectations and anxieties regarding Big Data among stakeholders and concludes that the community should take a more active role in understanding Big Data and influencing the governance of its usage.